Enhanced Production of (S)-2-arylpropionic Acids by Protein Engineering and Whole-Cell Catalysis - Liu, Xiaolong; Zhao, Meng; Fan, Xinjiong; Fu, Yao (Frontiers in Bioengineering and Biotechnology, 2021)
Esterases are important biocatalysts for chemical synthesis. Several bHSL family esterases have been used to prepare (S)-2-arylpropionic acids with stronger anti-inflammatory effects via kinetic resolution. Here, we presented the discovery of key residues that controlled the enantioselectivity of bHSL family esterases to ethyl 2-arylpropionates, through careful analysis of the structural information and molecular docking. A new bHSL family esterase, Est924, was identified as a promising catalyst for kinetic resolution of racemic ethyl 2-arylpropionates with slight (R)-stereopreference. Using Est924 as the starting enzyme, protein engineering was conducted at hotspots, and the substitution of A203 was proved to act on the enantioselectivity. The stereopreference of the mutant M1(A203W) was inverted to ethyl (S)-2-arylpropionates, and this stereopreference was further improved in variant M3(I202F/A203W/G208F). In addition, the optimal variant, M3, was also suitable for the resolution of ibuprofen ethyl ester and ketoprofen ethyl ester, and their efficient (S)-isomers were synthesized. Next, the whole-cell catalyst harboring M3 was used to prepare (S)-ketoprofen. (S)-ketoprofen with 86%ee was produced by whole-cell catalyst with a single freeze-thaw cycle, and the cell could be reused for at least 5 cycles. Our results suggested that Est924 variants could kinetically resolve economically important racemates for industrial production and further offer the opportunity for the rational design of enzyme enantioselectivity. Moreover, it is an economical process to prepare optically pure (S)-ketoprofen by using an engineered strain harboring M3 as the catalyst.